IMPLEMENTASI DIGITAL MARKETING TERHADAP EFEKTIVITAS PENJUALAN PADA UMKM GOLOK CIBATU SUKABUMI - Nabila, Rifqah; Suhud, Usep; Berutu, Meta Bara (Indonesian Journal of Economy, Business, Entrepreneuship and Finance, 2025)
Digital marketing has become an essential strategy for micro, small, and medium enterprises (MSMEs) to expand market reach and enhance sales performance in the digital era. This study aims to analyze the implementation process of digital marketing in Golok Cibatu MSMEs in Sukabumi, identify the opportunities and challenges faced by business owners, and assess the impact of digital marketing on sales effectiveness. This research employs a qualitative method with a field research approach, collecting data through observation, interviews, and documentation, and analyzing it using qualitative content analysis with the assistance of Nvivo15 software. The findings reveal that digital marketing is implemented adaptively by business owners, creating opportunities such as broader market reach, increased brand awareness, and stronger personal branding. However, several challenges remain, including platform policies, competition among MSMEs, and limited digital skills. The study confirms that digital marketing significantly contributes to improving sales effectiveness and fostering the business growth of Golok Cibatu MSMEs.